Pemetaan Sebaran Ruang Parkir Menggunakan Sistem Informasi Geografis di Kota Langsa (Studi Kasus: Kecamatan Langsa Barat) - Salsabila Zukhra; Wan Alamsyah; Arisna Fauzia (Journal of Innovative and Creativity, 2026)
Along with the increasing population growth in Langsa City, there is also a growing need to carry out various activities. Most residents of Langsa City choose to travel using private vehicles, which makes the need for parking spaces an important part of the transportation system. The distribution of parking spaces in Langsa City will be more effective and efficient if information related to their location is presented graphically. Geographic Information System (GIS) is a technology that can be used to process information related to distribution. This study aims to identify the distribution of parking spaces in Langsa City in accordance with the Guidelines for Planning and Operating Parking Facilities and present it on a distribution map. In addition, it also analyzes the parking characteristics of the Mangrove Forest Tourist Attraction. The research method was a direct survey at the research location to obtain the coordinates of the parking spaces and the number of vehicles parked in the tourist attraction parking spaces. The results of the study showed that there were 86 parking spaces in West Langsa District, 78 of which were identified as formal parking spaces and 8 parking spaces on the roadside which were identified as informal parking spaces. Mapping was carried out using a Geographic Information System (GIS) with ArcMap 10.8 software, which will present a map of the distribution of parking spaces in West Langsa District. The parking characteristics of the Mangrove Forest Tourist Attraction indicate that the parking index value (PI < 100%) means that the parking space capacity is not a problem and is still sufficient to accommodate the volume of vehicles, and there is no need for additional new parking spaces.